2017
DOI: 10.1002/mnfr.201600974
|View full text |Cite
|
Sign up to set email alerts
|

The atypical genesis and bioavailability of the plant-based small RNA MIR2911: Bulking up while breaking down

Abstract: Scope The uptake of dietary plant small RNAs (sRNAs) in consumers remains controversial, which is mainly due to low dietary content in combination with poor fractional absorption. MIR2911, among all the plant sRNAs including microRNAs, has been shown to be one of the most robustly absorbed sRNAs. Here we analyze the unusual abundance and unique genesis of MIR2911 during vegetable processing. Methods and Results Using qRT-PCR, the abundance of MIR2911 increased dramatically in macerated tissues while other mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“… Not mentioned RT-qPCR, Bioinformatic, Dual-luciferase reporter assay, Provided insights into the atypical bioavailability of miR2911 and offered engineering strategies for plant-based sRNA therapeutics. [ 147 ] 2015 Orally administered tumor suppressor miRNAs reduced tumor burden in Apc Min/+ mice and were detectable in intestinal tissue. miR34a, miR143, miR145 Synthesized methylated miRNAs Intestinal miR34a was at a detectable level; detection of miR143 and miR145 in mouse intestines were failed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… Not mentioned RT-qPCR, Bioinformatic, Dual-luciferase reporter assay, Provided insights into the atypical bioavailability of miR2911 and offered engineering strategies for plant-based sRNA therapeutics. [ 147 ] 2015 Orally administered tumor suppressor miRNAs reduced tumor burden in Apc Min/+ mice and were detectable in intestinal tissue. miR34a, miR143, miR145 Synthesized methylated miRNAs Intestinal miR34a was at a detectable level; detection of miR143 and miR145 in mouse intestines were failed.…”
Section: Introductionmentioning
confidence: 99%
“…Studies supporting biologically relevant uptake of plant-originated miRNAs have focused on miR2911, a honeysuckle-derived miRNA [ 29 , 144 147 ]. Honeysuckle is a well-known Chinese herb widely applied in the prevention and control of epidemic diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…others have provided additional evidence; xenomiRs can be identified in plasma in small retrospective data sets . Novel data suggests atypical behavior of certain miRNAs, for instance miR‐2911 concentration may be increased while other miRNAs become degraded . In one of the latest publications, Huang et al.…”
Section: Introductionmentioning
confidence: 99%
“…[18] Novel data suggests atypical behavior of certain miRNAs, for instance miR-2911 concentration may be increased while other miRNAs become degraded. [19] In one of the latest publications, Huang et al fed C57BL/six mice with corn and observed no substantial absorption of miRNA in the whole blood or changes in feces miRNA. [20] For the detailed summary we refer to several recent reviews dealing with the progress in the field.…”
Section: Introductionmentioning
confidence: 99%